Who was Frida Kahlo? - Fabiny, Sarah (Who was-- ?, 2013)
You can always recognize a painting by Kahlo because she is in nearly all--with her black braided hair and colorful Mexican outfits. A brave woman who was an invalid most of her life, she transformed herself into a living work of art. As famous.